Design of a brain-penetrant CDK4/6 inhibitor for glioblastoma. Issue 16 (15th August 2019) - Bronner, Sarah M.; Merrick, Karl A.; Murray, Jeremy; Salphati, Laurent; Moffat, John G.; Pang, Jodie; Sneeringer, Christopher J.; Dompe, Nicholas; Cyr, Patrick; Purkey, Hans; Boenig, Gladys de Leon; Li, Jun; et al.
Graphical abstract: Abstract: CDK4 and CDK6 are kinases with similar sequences that regulate cell cycle progression and are validated targets in the treatment of cancer. Glioblastoma is characterized by a high frequency of CDKN2A/CCND2/CDK4/CDK6 pathway dysregulation, making dual inhibition of CDK4 and CDK6 an attractive therapeutic approach for this disease. Abemaciclib, ribociclib, and palbociclib are approved CDK4/6 inhibitors for the treatment of HR+/HER2− breast cancer, but these drugs are not expected to show strong activity in brain tumors due to poor blood brain barrier penetration. Herein, we report the identification of a brain-penetrant CDK4/6 inhibitor derived from a literature molecule with low molecular weight and topological polar surface area (MW = 285 and TPSA = 66 Å 2 ), but lacking the CDK2/1 selectivity profile due to the absence of a basic amine. Removal of a hydrogen bond donor via cyclization of the pyrazole allowed for the introduction of basic and semi-basic amines, while maintaining in many cases efflux ratios reasonable for a CNS program. Ultimately, a basic spiroazetidine (cp K a = 8.8) was identified that afforded acceptable selectivity over anti-target CDK1 while maintaining brain-penetration in vivo (mouse K p, uu = 0.20–0.59). To probe the potency and selectivity, our lead compound was evaluated in a panel of glioblastoma cell lines. Potency comparable to abemaciclib was observed in Rb-wild type lines U87MG, DBTRG-05MG, A172, and T98G, while Rb-deficient cell lines SF539 and M059J exhibited a lack of sensitivity.